PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, SISTEM INFORMASI AKUNTANSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKERDITAN DESA (LPD) SEKECAMATAN PENEBEL - I Gede Made Merta Sedana; Ni Komang Sumadi; Rai Dwi Andayani W (UNHI Press, 2021)
LPD or village credit institutions are non-bank financial institutions that help villages and village communities manage their finances. The purpose of this study was to examine the effect of transformational leadership style, accounting information systems and motivation on employee performance at the Village Perkerditan Institute (LPD) of Penebel Subdistrict. The population used in this study were all 113 LPD employees in the Penebel District. Determination of the sample using purposive sampling method in order to get 74 people as a sample. After the instrument test and classical assumption test were carried out, the data analysis was then carried out using multiple linear regression analysis, determination, t test, and F test. The results of the analysis showed that transformational leadership style had a positive and significant effect on employee performance at the Village Credit Institution (LPD). Penebel sub-district. The accounting information system has a positive and significant effect on employee performance at the Village Credit Institution (LPD) in Penebel sub-district. Motivation has a positive and significant effect on employee performance at the Village Credit Institution (LPD) in Penebel sub-district.